A WD40-repeat protein unique to malaria parasites associates with adhesion protein complexes and is crucial for blood stage progeny. (December 2015) - Bohl, Andreas; Kuehn, Andrea; Simon, Nina; Ngongang, Vanesa; Spehr, Marc; Baumeister, Stefan; Przyborski, Jude; Fischer, Rainer; Pradel, Gabriele
Abstract Background During development in human erythrocytes, Plasmodium falciparum parasites display a remarkable number of adhesive proteins on their plasma membrane. In the invasive merozoites, these include members of thePf MSP1 andPf AMA1/RON complexes, which facilitate contact between merozoites and red blood cells. In gametocytes, sexual precursor cells mediating parasite transmission to the mosquito vector, plasma membrane-associated proteins primarily belong to thePf CCp and 6-cys families with roles in fertilization. This study describes a newly identified WD40-repeat protein unique toPlasmodium species that associates with adhesion protein complexes of both merozoites and gametocytes. Methods The WD40-repeat protein-like proteinPf WLP1 was identified via co-immunoprecipitation assays followed by mass spectrometry and characterized using biochemical and immunohistochemistry methods. Reverse genetics were employed for functional analysis. Results Pf WLP1 is expressed both in schizonts and gametocytes. In mature schizonts, the protein localizes underneath the merozoite micronemes and interacts withPf AMA1, while in gametocytesPf WLP1 primarily accumulates underneath the plasma membrane and associates withPf CCp1 andPf s230. Reverse genetics failed to disrupt thepfwlp1 gene, while haemagglutinin-tagging was feasible, suggesting a crucial function forPf WLP1 during blood stage replication. Conclusions This is the first report on a plasmodial WD40-repeat protein associating with cell adhesion proteins. Since WD40 domains are known to mediate protein–protein contact by serving as a rigid scaffold for protein interactions, the presented data suggest thatPf WLP1 supports the stability of adhesion protein complexes of the plasmodial blood stages.